Кинематическая модель движения колёсной пары после схода с рельс - Петухов, Вадим Михайлович; Аксёнова, Наталья Анатольевна (НТУ "ХПИ", 2017)
Определена траектория движения колесной пары вагона после ее схода с рельс. Построена кинематическая модель движения колеса по шпальной решетке. Выполнен кинематический анализ движения колеса по шпалам. Получено аналитическое выражение, связывающее движение колеса с параметрами верхнего строения пути. Показано, что амплитуда и частота колебаний колесной пары при ее сходе зависят от диаметра колеса, ширины горизонтальной поверхности шпалы и расстояния между осями шпал. Определены мгновенные центры скоростей колеса в характерных точках. Разработанная кинематическая модель определяет основные диагностические признаки схода вагонов с рельс. Это позволит создать надежный алгоритм распознавания схода для построения аппаратного и программного обеспечения технической системы контроля сходов вагонов с рельс.

Kinematic analysis of the movement of a wagon wheel pair after its derailment is performed. Based on the studies carried out, the following results were obtained. The trajectory of motion of the center of the wheel after its coming off the rail along the sleeper grating is determined graphically. The center of the wheel moves rectilinearly along the horizontal section of the sleeper and along the arc of the circle in the areas where the wheel rolls from a sleeper and hits the next one. Thus, the trajectory of motion looks like a cyclic combination of rectilinear segments and segments of circles. An analytic expression characterizing wagon derailment is obtained, which connects the parameters of the upper structure of the track (the sleeper grid) and the wheel. The motion of the center of the wheel is determined by different equations depending on the stages of motion. The law of motion is given by different functions corresponding to different motion stages. It is shown that the amplitude and frequency of oscillations of a wheel pair at its derailment depend on the diameter of the wheel, the width of the horizontal surface of the sleeper and the distance between the axes of the sleepers. Instantaneous centers of wheel velocities at characteristic points are determined. The development of a kinematic model of the movement of a wagon wheel pair after its derailment allows one to proceed constructing a dynamic model of such a motion. The ultimate goal of studying this process should be the construction of a diagnostic model for the derailment of wagons based on the presented kinematic and dynamic models. This will make it possible to create a reliable derailment recognition algorithm for constructing the hardware and software of a wagon derailment technical control system.
Kinematic model of wheel pair motion after its derailment
Keywords: колесо; кинематический анализ; диагностическая модель; траектория; wheel; kinematic analysis; diagnostic model; trajectory